The Oxford handbook of health care management - Ferlie, Ewan, 1956-; Montgomery, Kathleen, 1946-; Reff Pedersen, Anne, 1970- (Oxford handbooks online., 2016)
The Handbook provides an authoritative overview of current issues and debates in the field of health care management. It contains over twenty chapters from well known and eminent academic authors internationally, selected for their expertise and asked to provide a broad and critical overview of developments in their particular topic area. The development of an international perspective and body of knowledge is a key feature of the book. The Handbook secondly makes a case for bringing back a social science perspective into the study of the field of health care management. It therefore contains a number of contrasting and theoretically orientated chapters (e.g. on institutionalism; critical management studies).